ANALISIS HUBUNGAN ANTARA KECERDASAN LOGIS MATEMATIS DENGAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Faridah Bahiyatun Nisa; Mohammad Mukhlis; Maswar Maswar (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2020)
This study examined the relationship of logical intelligence students' mathematical communication skills. This research was conducted at the senior high school of Jenggawah at the even semester of the 2019/2020 academic year. The population in this study were all of the high school students of class X IPA, the total students were 144 students in the 2019/2020 academic year. The sampling technique of this study was using 64 Randoms Cluster Sampling as well as the instruments used in the form of mathematical logical intelligence questionnaire and mathematical communication skills test questions. The Analysis of the data used in this research was descriptive and inferential analysis by using a simple linear regression test. Based on the results of a simple linear regression test that the results of the relationship of mathematical logical intelligence of mathematical communication skills can be seen from t count = 11.074 > t table = 1.997 with a significance of 0.000 < 0.05, it could be concluded that there was a relationship of mathematical logical intelligence to mathematical communication ability.